THERAPEUTIC EFFECTS OF EXTRACTS OF ANNONA SENEGALENSIS AND EUCALYPTUS CAMALDULENSIS IN EXPERIMENTAL AFRICAN TRYPANOSOMIASIS. - Ogbadoyi, E. O.; Kabiru, A.; Salako, A.; Okogun, J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Human African trypanosomiasis caused by trypanosome is 100% fatal if untreated. Currently chemotherapy, is the major control measure but it is grossly inadequate.Thus there is an urgent need for new drugs. Leaves, stem and root barks of Annona senegalensis and Eucalyptus camaldulensis were sequentially extracted with hexane, ethylacetate, methanol and water. Administration of crude and partially purified aqueous extracts of A. senegalensis leaves at a dose of 200 mg/kg BW to mice experimentally infected with Trypanosoma brucei cured the experimental infection. Blood and cerebrospinal fluid (CSF) infectivity tests failed to produce any infection 2 months after subinnoculation of blood and CSF from the cured mice into healthy mice [1]. Hexane and aqueous extracts of the stem bark of A. senegalensis also cured experimental T. brucei infection in mice. Hexane, ethylacetate, and methanol extracts of leaves of E. camaldulensis each administered at a dose of 200mg/kg BW all cured experimental T. brucei infection in mice. Similarly blood and CSF infectivity tests failed to produce infection in mice. Administration of a combination of methanolic extracts of the leaves of A. senegalensis and E. camaldulensis completely cured experimental T. brucei infection in mice. We conclude that the extracts of A. senegalensis and E. camaldulensis used in combination therapies have enormous potentials of overcoming drug resistance problem in sleeping sickness chemotherapy.